Effects of synergism in mixes of surfactants - Ледовських, В. М.; Приходченко, П. Г. (Proceedings of National Aviation University (archive), 2021)
Phenomenons of synergism in mixes of surfactants were researched. Reasons of effects of synergism in mixes of surfactants may be various. It was determined that phenomenon of synergism may be obsen ed in mixes of surfactants those are different in their electric nature, in geometric sizes (consist of high-molecular and low-molecular surfactants), in a mechanism of does of individual components in mixes on a moti эп of separate electrochemical reactions of metal’s corrosion (mixes of no organic passivators and adsofptive organic surfactants; mixes those provide inhibition of anodic reaction (ionization of metal) and accele ating of cathode reaction). Super additive intensification of surfactant’s does in mixes due to formation of si rface layers with high, near limited extent of surface’s infill was observed. This point of view is confirmee with the same character of surface activity on the interfaces solution-air, solution-mercury, and solution solid metal for surface-active cations and anions, their mixes. Surface activity increases due to arising of attr; ictive interaction among ions with different charges ((+) and (-)) instead of repulsive interaction among ion: with the same charge ((+) and (+) or (-) and (-)).